Carbon nanotube (CNT) metal composites exhibit greatly reduced radiation damage. (15th January 2021) - Cao, Penghui; So, Kang Pyo; Yang, Yang; Park, Jong Gil; Li, Mingda; Yan, Long; Hu, Jing; Kirk, Mark; Li, Meimei; Lee, Young Hee; Short, Michael P.; Li, Ju
Graphical abstract: Abstract: Radiation damage of structural materials leads to mechanical property degradation, eventually inducing failure. Secondary-phase dispersoids or other defect sinks are often added to materials to boost their radiation resistance. We demonstrate that a metal composite made by adding 1D carbon nanotubes (CNTs) to aluminum (Al) exhibits superior radiation resistance. In situ ion irradiation with transmission electron microscopy (TEM) and atomistic simulations together reveal the mechanisms of rapid defect migration to CNTs, facilitating defect recombination and enhancing radiation tolerance. The origin of this effect is an evolving stress gradient in the Al matrix resulting from CNT transformation under irradiation, and the stability of resulting carbides. Extreme value statistics of large defect behavior in our simulations highlight the role of CNTs in reducing accumulated damage. This approach to controlling defect migration represents a promising opportunity to enhance the radiation resistance of nuclear materials without detrimental effects.